A highly sensitive “switch-on” fluorescent probe for protein quantification and visualization based on aggregation-induced emission - Wang, Fangfang; Wen, Jiying; Huang, Lingyun; Huang, Jinjiu; Ouyang, Jin (Chemical communications (Cambridge, England), 2012)
A highly sensitive and water-soluble "switch-on" fluorescent probe with aggregation-induced emission characteristics was developed for protein quantification and visualization. It offers a rapid, economic and effective way for the assay of complete serum proteins and disease-marker proteins.